The Effect of Padlet-Based KWL Reading Strategy on Senior Highschool Students’ Reading Comprehension In Report Text - Tantri Frista Hapsari; Yuri Lolita (English Education:Journal of English Teaching and Research, 2026)
The objective of this research was to determine the significant difference in students’ reading comprehension achievement between students taught using the Padlet-based Know-Want to Know-Learned (KWL) chart strategy and those taught using a conventional reading strategy.A quantitative method with a quasi-experimental design was employed with the participants involving the students in English reading lesson.  The samples taken using purposive sampling numbered 36 for the experimental class and 36 for the control class. After the pretest and posttest were conducted, the data obtained showed an increase in the average English proficiency of the experimental class students from 69.22 to 91.11. This indicates that the students' reading skills increased significantly after the treatment was conducted. Although the statistical analysis did not reveal a significant difference between the experimental and control groups, the experimental group taught using the Padlet-based KWL chart strategy demonstrated a higher mean gain score and a larger effect size. Nevertheless, the experimental group taught using the Padlet-based KWL chart strategy demonstrated a higher mean gain score and a larger effect size, indicating that the strategy still had a meaningful practical impact on students’ reading comprehension despite the absence of statistical significance.